Innovative Application of New Chinese Leather Women's Bag Design based on Multimodal Fusion - Lingling LIU; Huanna FU; Biao MA (Pige Kexue Yu Gongcheng)
In order to explore the intelligent and innovative application of new Chinese style and promote the modern design transformation of traditional culture, the female bag design was analyzed as an example. Firstly, the relationship between new Chinese style, leather women's bags and intangible cultural heritage was analyzed to summarize the way of expression and cultural connotation of the application of new Chinese style in the design of women's leather bags. Secondly, the multimodal fusion theory was applied to extract the features of new Chinese style women's bags and establish a demonstration library. Then, genetic algorithms were applied to fuse the features and output the design proposal. Lastly, the fusion of the non-heritage elements of summer cloth and bamboo weaving and the leather bags was taken as an example for design practice to verify the effectiveness of the bag design method combining multimodal fusion and genetic algorithm. This work provides a theoretical method for the research of intelligent design of new Chinese leather women’s bags, as well as a new idea for the dissemination of intangible cultural heritage.